Structure and expression of an ethylene-related mRNA from tomato. - Holdsworth, M J (1987)
Messenger RNAs homologous to a cDNA clone (pTOM 13) derived from a ripe-tomato-specific cDNA library are expressed during tomato fruit ripening and after the wounding of leaf and green fruit material. Both responses involve the synthesis of the hormone ethylene. Accumulation of the pTOM 13--homologous RNA during ripening is rapid and sustained, and reaches its maximum level in orange fruit. Following mechanical wounding of tomato leaves a pTOM 13--homologous RNA shows rapid induction within 30 minutes, which occurs before maximal ethylene evolution (2-3 h). This RNA also accumulates following the wounding of green tomato fruit. Northern blot analysis of poly(A)+ RNA indicates that the length of the mRNA is about 1400 nucleotides. Nucleotide sequence analysis showed the cDNA insert to contain the complete coding region of the pTOM 13 protein (33.5 kD) and an unusual 5' structure of ten dT-nucleotides. Hybridisation of the pTOM 13 cDNA insert to Southern blots of tomato DNA indicates the presence of only a small number of homologous sequences in the tomato genome.